PENYEBAB PERBEDAAN TARIF INA-CBGs PADA KASUS SECTIO CAESAREAN DENGAN INDIKASI MALPRESENTASI DI RSUD TUGUREJO KOTA SEMARANG TAHUN 2018 - Faik Agiwahyuanto; Indriati - - (Dian Nuswantoro Semarang, 2020)
Caesarean sectio action was a surgical activity carried out through the slicing of the abdominal wall which will later be used to remove the fetus. Based on the results of the initial survey, it shows that the percentage rate in one year in caesarean sectio at Tugurejo Regional Hospital Semarang is 29%, it shows that the percentage of caesarean sectio measures has not met the WHO standard of 5-15% in one year. Caesarean sectio was performed based on medical indications, in Semarang Tugurejo Regional Hospital there were 39 indications of malpresentations that were carried out by sectional caesarean actions 2018. The research design wass descriptive study with an observation method on the DRM and the patient claim result sheet for Caesarean section. Data collection techniques using documentation. Data sources use secondary data. Data samples were 39 cases of caesarean sectio with indication of malpresentation. Data analysis uses univariate or percentage techniques. The results of the study were the rates of INA-CBGs in caesarean sectio patients affected by primary diagnoses, secondary diagnoses, and actions that can affect the INA-CBGs code on severity level or severity of patients, and the class of patient care while supporting examinations do not affect INA-CBGs rates in a manner live.Keywords: Causing, difference, tariffs INA-CBGs, Sectio Caesarean,Malpresentations